Damage characterization of stiffened glass-epoxy laminates under tensile loading with acoustic emission monitoring. (15th August 2018) - Arumugam, V.; Saravanakumar, K.; Santulli, C.
Abstract: The design of composite components in the aerospace industry often includes structural discontinuities, such as cutouts, for functional requirements like ventilation, tunnel passage, maintenance and repair. The presence of cutout holes leads to complicated stress concentrations with a substantial reduction in structural stability and strength of the resulting composites. It is known that reinforcing with additional material at the cutout zones can extend the damage tolerance of a structure, therefore maintaining structural integrity and load carrying capacity. This study focuses on the experimental investigation of the tensile behavior and failure characteristics of stiffened glass/epoxy composite laminates, with cutouts, under acoustic emission monitoring. The progressive failure mechanisms of laminates with cutouts and the potential benefits of additionally dropped reinforcements are evaluated under tensile loading. The additional reinforcements were provided in either a step-like or as a simultaneous drop-off sequence between adjacent continuous plies. Results showed that adding ply drop reinforcements at the location of the cutout hole improves the stiffness, strength, and also prolongs the life of the composite laminates. It is also observed that step-like ply drop arrangements performed more effectively than simultaneously dropped configurations. The location and extent of damage identified by microscopic images correlated well with the acoustic emission results.